Simulation of thermal processes on the electrode of a miniature protective spark gap - Murog, Igor A.; Gnido, Valery F.; Tinina, Elena V.; Ilchuk, Igor A.; Asayeva, Tatiana A. (Journal of the University of Zulia, 2021)
The article discusses the issues that arise when determining the temperature in the region of the cathode spot in miniature protective spark gaps. The modeling principle is used to study the temperature field on the spark gap electrode. A mathematical model of the process is compiled on the basis of the balance of power entering the cathode spot and its removal inside the cathode due to thermal conductivity. A numerical solution of the obtained nonlinear heat equation with inhomogeneous boundary conditions by the finite-difference method is presented. The authors compared the found temperatures in the cathode spot for metals of the fourth and fifth groups of the Mendeleev’s Periodic Table with the corresponding melting points of the selected metals. A complete correlation was obtained between these temperatures. Simulation of thermal processes in the region of the cathode spot on the electrode made of 42NA-VI alloy has been carried out. The results are presented in the form of diagrams.